Strategies to improve the ovarian response to equine pituitary extract in cyclic mares - Scoggin, C. F.; Meira, Cezinande de [UNESP]; McCue, P. M.; Carnevale, E. M.; Nett, T. M.; Squires, E. L. (Elsevier B.V., 2002)
Equine pituitary extract (EPE) has been reported to induce heightened follicular development in mares, but the response is inconsistent and lower than results obtained in ruminants undergoing standard superovulatory protocols. Three separate experiments were conducted to improve the ovarian response to EPE by evaluating: (1) effect of increasing the frequency or dose of EPE treatment; (2) use of a potent gonadotropin-releasing hormone agonist (GnRH-a) prior to EPE stimulation (3) administration of EPE twice daily in successively decreasing doses. In the first experiment. 50 mares were randomly assigned to one of four treatment groups. Mares received (1) 25 mg EPE once daily; (2) 50 mg EPE once daily (3) 12.5 mg EPE twice daily; or (4) 25 mg EPE twice daily. All mares began EPE treatment 5 days after detection of ovulation and received a single dose of cloprostenol sodium 7 days postovulation. EPE was discontinued once half of a cohort of follicles reached a diameter of greater than or equal to35 mm and hCG was administered. Mares receiving 50 mg of EPE once daily developed a greater number (P = 0.008) of preovulatory follicles than the remaining groups of EPE-treated mares, and more (P = 0.06) ovulations were detected for mares receiving 25 mg EPE twice daily compared to those receiving either 25 mg EPE once daily and 12.5 mg EPE twice daily. Embryo recovery per mare was greater (P = 0.05) in the mares that received 12.5 mg EPE twice daily than those that received 25 mg EPE once daily. In Experiment 2, 20 randomly selected mares received either 25 mg EPE twice daily beginning 5 days after a spontaneous ovulation. or two doses of a GnRH-a agonist upon detection of a follicle greater than or equal to35 mm and 25 mg EPE twice daily beginning 5 days after ovulation. Twenty-four hours after administration of hCG, oocytes were recovered by transvaginal aspiration from all follicles greater than or equal to35 mm. No differences were observed between groups in the numbers of preovulatory follicles generated (P = 0.54) and oocytes recovered (P = 0.40) per mare. In Experiment 3, 18 mares were randomly assigned to one of two treatment groups. Then, 6-11 days after ovulation, mares were administered a dose of PGF(2gamma) and concomitantly began twice-daily treatments with EPE given in successively declining doses, or a dose of PGF(2alpha), but no EPE treatment. Mares administered EPE developed a higher (P = 0.0004) number of follicles :35 mm, experienced more (P = 0.02) ovulations, and yielded a greater (P = 0.0006) number of embryos than untreated mares. In summary, doubling the dose of EPE generated a greater ovarian response, while increasing the frequency of treatment, but not necessarily the dose. improved embryo collection. Additionally, pretreatment with a GnRH-a prior to ovarian stimulation did not enhance the response to EPE or oocyte recovery rates. (C) 2002 Elsevier B.V. All rights reserved.
Keywords: superovulation; mare; equine pituitary extract; GnRH-agonist